2008
DOI: 10.1373/clinchem.2007.100412
|View full text |Cite
|
Sign up to set email alerts
|

Two Mass-Spectrometric Techniques for Quantifying Serine Enantiomers and Glycine in Cerebrospinal Fluid: Potential Confounders and Age-Dependent Ranges

Abstract: BACKGROUND:The recent discovery and specific functions of D-amino acids in humans are bound to lead to the revelation of D-amino acid abnormalities in human disorders. Therefore, high-throughput analysis techniques are warranted to determine D-amino acids in biological fluids in a routine laboratory setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…The residue was dried and prepared to form methyl ester-pentafluoropropyl ether/amide derivatives for analysis according to the method of Fuchs et al (23). The dried samples were first treated with acetyl chloride-methanol (1:4 [vol/vol[; 100 l; 70°C for 45 min) and dried.…”
mentioning
confidence: 99%
“…The residue was dried and prepared to form methyl ester-pentafluoropropyl ether/amide derivatives for analysis according to the method of Fuchs et al (23). The dried samples were first treated with acetyl chloride-methanol (1:4 [vol/vol[; 100 l; 70°C for 45 min) and dried.…”
mentioning
confidence: 99%
“…excellent 2 s temporal response for D-amino acids and will likely be useful for investigating rapid events relating to D-ser dynamics in brain. Several recent HPLC studies have reported powerful tandem MS detection after precolumn derivatization of D-amino acids in biological samples [33,61,64]. D-ser, D-asp, and D-glu levels have been studied in rat and Aplysia CNS by these approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification was carried out by MS/MS in SRM mode with a reported 0.095 lM LOD. The approach was recently adapted to triple quadrupole by Fuchs and colleagues in negative ion spray mode and selective ion monitoring (SIM) [33]. Gradient elution using a C-18 column (3.96150 mm, 3 lm) allowed for quantification of glycine in addition to D,Lser.…”
Section: Song and Colleagues Recently Developed A Micro-hplc Approachmentioning
confidence: 99%
“…Therefore, high-throughput analysis techniques are necessary to determine D-AAs in biological fluids and tissues [56]. Fuchs et al developed and validated two chromatographic methods, i.e., GC-MS and LC-MS for the determination of D-Ser, L-Ser, and glycine (Gly) in cerebrospinal fluid (CBF) [56]. Pentafluoropropionic anhydride was used for sample derivatization before CG analysis.…”
Section: Chromatographic Methods For Aa Determination In Biological Smentioning
confidence: 99%